Augmented Reality for Geospatial in E-Tourism: Current Status, Research Trends, and Future Directions - Johan Reimon Batmetan; Trudi Komansilan; Sondy Kumajas; Hiskia Kamang Manggopa (International Journal of Information Technology and Education, 2022)
This study discusses the implementation of augmented reality in e-tourism and examines the current state of research on the topic and presents various inventions or innovations of augmented reality in tourism. These findings will provide insight for further research and experimentation opportunities that are aligned with the development of augmented reality for e-tourism in the future. There are a lot of data, models, and innovations about augmented reality that have been published in different and complex ways. It has explained the overall picture of augmented reality. The purpose of this research is to analyze and identify data sets, research trends, and methods that have been used since 2017. We use a systematic literature review method. We carry out the process of identifying, assessing, and interpreting research evidence and reviewing the literature to answer specific research questions. We conducted the analysis by selecting the main study in the field of augmented reality on e-tourism. We have mapped trends, data sets, and methods on augmented reality implemented in e-tourism. This study concludes that we have successfully identified and analyzed research trends in augmented reality in a measurable and systematic way in the last 5 years.